Dorsal and ventral striatal functional connectivity shifts play a potential role in internet gaming disorder - Guang-Heng Dong (Nature Portfolio, 2021)
In order to shed light on the underlying neural mechanisms of internet gaming disorder (IGD), Dong et al collected longitudinal resting-state fMRI data from participants with IGD or those who partake in recreational game use. They demonstrated that, consistent with animal models of addiction, dorsal and ventral striatal functional connectivity shifts appeared to play a potential mechanistic role in IGD.